Successful radiofrequency ablation of liver metastases from prostate cancer. Issue 6 (5th August 2022) - Hino, Daichi; Sugano, Takahiro; Kino, Mika; Nakata, Takako; Kito, Hiroki; Inoue, Masafumi; Fujie, Hajime; Akakura, Koichiro
Abstract : Introduction: Patients with liver metastases from prostate cancer show poor prognosis. We performed metastases‐directed therapy using radiofrequency ablation of liver metastases in an attempt to improve the prognosis in a patient with metastatic prostate cancer. Case presentation: We present the case of a 66‐year‐old man who was treated for metastatic castration‐resistant prostate cancer. Evaluation showed isolated liver metastases together with elevated serum prostate‐specific antigen levels. We performed metastases‐directed therapy using radiofrequency ablation of the liver tumor. The patient showed no recurrent liver metastases for 42 months and survived for 66 months after diagnosis of metastatic prostate cancer. Conclusion: To our knowledge, this is the first report that describes radiofrequency ablation of liver metastases from prostate cancer. This procedure may be a useful therapeutic option for metastases‐directed therapy in patients with liver metastases from prostate cancer.